2023
DOI: 10.3390/metabo13010084
|View full text |Cite
|
Sign up to set email alerts
|

Magnolol as a Protective Antioxidant Alleviates Rotenone-Induced Oxidative Stress and Liver Damage through MAPK/mTOR/Nrf2 in Broilers

Abstract: This study aimed to investigate the protective effects and molecular mechanism of magnolol supplementation on rotenone-induced oxidative stress in broilers. Two hundred and eighty-eight old male AA broilers were randomly divided into four groups: the CON group: basic diet with sunflower oil injection; the ROT group: basic diet with 24 mg/kg BW rotenone; the MAG+ROT group: basic diet with 300 mg/kg magnolol and rotenone injection; and the MAG group: basic diet with 300 mg/kg magnolol and sunflower oil injection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
(35 reference statements)
0
2
0
Order By: Relevance
“…Recently, magnolol has emerged as an effective and safe feed additive to enhance health and growth in livestock production. Dietary magnolol supplementation in chickens has been reported to enhance growth performance [ 23 ], exert anti-inflammatory and antioxidant effects [ 24 , 25 ], increase villus height [ 26 ], promote intestinal barrier function [ 27 ], and regulate glucose and lipid metabolism [ 28 ]. Despite sharing common characteristics with other polyphenols, the potential of magnolol to regulate AA transporters and thereby enhance the absorption or deposition of AAs to promote animal growth remains uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, magnolol has emerged as an effective and safe feed additive to enhance health and growth in livestock production. Dietary magnolol supplementation in chickens has been reported to enhance growth performance [ 23 ], exert anti-inflammatory and antioxidant effects [ 24 , 25 ], increase villus height [ 26 ], promote intestinal barrier function [ 27 ], and regulate glucose and lipid metabolism [ 28 ]. Despite sharing common characteristics with other polyphenols, the potential of magnolol to regulate AA transporters and thereby enhance the absorption or deposition of AAs to promote animal growth remains uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…Xie et al reported that MAG enhanced the growth performance and meat quality of broilers by improving their antioxidant and gut microbiota homeostasis [ 15 ]. Moreover, MAG also relieves oxidative stress and liver injury via the MAPK/mTOR/Nrf2 signaling pathway [ 16 ]. Furthermore, dietary supplementation with MAG improved hen performance, egg production, and egg quality [ 17 ].…”
Section: Introductionmentioning
confidence: 99%